Girl or boy? A study on Mexican parents’ preferences for the sex of their children - Méndez Ruiz, Andrés; Campos Vázquez, Raymundo M. (Estudios Económicos de El Colegio de México, 2013)
Among Mexican parents child gender has an effect on family structure and fertility decisions. A first-born daughter increases the probability of father absence, of maternal custody in case of marital dissolution, of having more children and of a shorter elapsed period before a new child is born. The collection of evidence suggests that those effects are the result of a preference for sons among parents and not the result of other causes that could explain some of the results separately.